Situational Leadership, School of Organizational Climate Teacher Work and Performance Motivation - Ni Putu Nina Eka Lestari; Putu Eka Artha Pratama Putra; A.A.N. Oka Suryadinatha Gorda; A.A.N. Eddy Supriyadinata Gorda (Enrichment : Journal of Management, 2020)
This study aims to determine the influence of situational leadership on work motivation of private high school teachers, to determine the effect of organizational climate on work motivation of private high school teachers, to determine the effect of situational leadership on the performance of private high school teachers, to determine the effect of organizational climate on the performance of private high school teachers, to know the effect of work motivation on the performance of private high school teachers in Denpasar City. The number of samples in this study were 100 using the quota sampling method. Data collection using a questionnaire. This type of research is quantitative. The data analysis technique uses a structural equation method, using the AMOS application. The results showed that the influence of organizational climate has a significant positive effect on the work motivation of private high school teachers, situational leadership has a positive and significant effect on the performance of private high school teachers, organizational climate has a positive and significant effect on the performance of private high school teachers, work motivation has a positive and significant effect on the performance of high school teachers. Private sector in Denpasar.